RESPOSTA DE CULTIVARES DE ALGODÃO A APLICAÇÃO FOLIAR DE AZOSPIRILLUM BRASILENSE E NANOPARTICULAS DE CARBONO - Santos de Oliveira , Isabella; Vitor Ferreira Guedes, João; Marcéli Vasconcelos Rezende, Thais; Steiner , Fábio (ANAIS DO ENIC, 2026)
-